The challenges of measuring physical activity and sedentary behaviour in people with rheumatoid arthritis. Issue 1 (24th January 2023) - Steultjens, Martijn; Bell, Kirsty; Hendry, Gordon
Abstract: The importance of sufficient moderate-to-vigorous physical activity as a key component of a healthy lifestyle is well established, as are the health risks associated with high levels of sedentary behaviour. However, many people with RA do not undertake sufficient physical activity and are highly sedentary. To start addressing this, it is important to be able to carry out an adequate assessment of the physical activity levels of individual people in order that adequate steps can be taken to promote and improve healthy lifestyles. Different methods are available to measure different aspects of physical activity in different settings. In controlled laboratory environments, respiratory gas analysis can measure the energy expenditure of different activities accurately. In free-living environments, the doubly labelled water method is the gold standard for identifying total energy expenditure over a prolonged period of time (>10 days). To assess patterns of physical activity and sedentary behaviour in daily life, objective methods with body-worn activity monitors using accelerometry are superior to self-reported questionnaire- or diary-based methods. Lay Summary: What does this mean for patients? Sufficient physical activity and limited time spent being inactive (i.e. sedentary behaviour) are key to a healthy lifestyle for people with RA. Various methods are available to measure physical activity and sedentary behaviour. To show patterns of sedentary behaviour and light, moderate and vigorous physical activity over a period of 5–10 days, body-worn activity monitors provide more useful information than questionnaires. This information can be used to set activity goals for a healthier lifestyle.